Нарны идэвхт үзэгдлийн физик параметрүүдийг CFM аргаар тодорхойлоход үүсгүүрийн функцэд оптик зузааныг тооцох - Ч, Мөнхжаргал; Д, Батмөнх; Б, Батбаяр (Scientific transaction of the National University of Mongolia. Physics, 2022)
We presented some results about the physical parameters, derived with the cloud model taking into account the dependence of source function on the optical depth for solar absorption features. The dependence of source function on the optical depth is represented in the form Sv(tv) = a( 1 + tn v). The parameter fitting is achieved by iterative Levcnberg-Marquardt method for nonlinear dependences. The results of calculation were compared with the results obtained with the constant source function. Our results show that the dependence of source function on the optical depth very strongly influences the values of the optical thickness. Therefore because of decrease of the optical thickness the arch-filament system became thin than with constant source function. From the calculation for the filaments shows that the greatly reduced values of N2 ,Ne, and vice versa, Te increases.